2021
DOI: 10.1007/s42488-021-00050-6
|View full text |Cite
|
Sign up to set email alerts
|

The implication of business intelligence in risk management: a case study in agricultural insurance

Abstract: The increasing data scales in today’s business sectors coupled with the necessity of risk management raise the importance of business intelligence tools as an integrated solution for the insurance industry. These tools have mostly been used to achieve effective risk management. Although methods of risk management in the insurance industry have been proposed many years ago, the research effort has primarily been focused on predictive analyses. This study aimed to investigate the role of business intelligence as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, Paradza and Daramola (2021) concluded that through the use of BI, a company can improve organisational process, executive management decisionmaking, knowledge management, and risk management. Additionally, by managing risks, businesses can handle potential problems and ensure the success of their projects (Akcay, 2021;Luo et al, 2022), and BI tools can improve risk management, providing a 360-degree risk overview that allows the organisation to identify and mitigate these risks effectively (Amini et al, 2021). Decision making is a key to business and project success in any sector, especially in construction that requires the handling and management of various information and knowledge, and various systems and methods for decision support are emerging (Zhu et al, 2021).…”
Section: Business Intelligence and Construction Companiesmentioning
confidence: 99%
“…Furthermore, Paradza and Daramola (2021) concluded that through the use of BI, a company can improve organisational process, executive management decisionmaking, knowledge management, and risk management. Additionally, by managing risks, businesses can handle potential problems and ensure the success of their projects (Akcay, 2021;Luo et al, 2022), and BI tools can improve risk management, providing a 360-degree risk overview that allows the organisation to identify and mitigate these risks effectively (Amini et al, 2021). Decision making is a key to business and project success in any sector, especially in construction that requires the handling and management of various information and knowledge, and various systems and methods for decision support are emerging (Zhu et al, 2021).…”
Section: Business Intelligence and Construction Companiesmentioning
confidence: 99%
“…The BIS term was first used in 1958 by Hans Peter Luhn to identify tools for data analysis (Amini et al , 2021). Otherwise, many researchers believe that it was first used by Dresner in 1989 for describing a concept and methodologies for improvement of business decisions using facts and information from supporting systems (Phillips-Wren et al , 2021).…”
Section: Literature and Theoretical Foundationsmentioning
confidence: 99%
“…[ 45,46] 3. Adaptive learning systems Each discipline is meant to be designed as a workflow for a certain application area made of modules reflecting the necessary areas of knowledge, based on the ideas of "knowledge areas" and "application areas."…”
Section: Predictive Modelsmentioning
confidence: 99%